A Strategies To Practice English Conversation - Siregar, Nur Fadiah Arifah Siregar (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The practice conversation method is important for students' development in understanding and practicing English conversations in real life, by always practicing with other people daily. This research aims to show whether. The practice teaching method influences students' speaking achievement. The research was conducted in North Sumatra State Islamic University for 2nd-semester students in 2024 consisting of 28 students. Most of the students are embarrassed to practice conversations in English, making them look like they are not confident or don't memorize much English vocabulary, but they are still enthusiastic about carrying out several practice conversations. Practice conversation exercises can effectively show students' concern for their English performance. It tends to be revealed that showing conversations using English has an impact on student's English language skills